ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN BAGIAN ADMINISTRASI: STUDI KOMPARASI ANTARA WORK FROM OFFICE DAN WORK FROM HOME - Eline Octoviana Hutubessy (P3M Politeknik Negeri Ambon, 2025)
The digital transformation accelerated by the COVID-19 pandemic has fundamentally changed organizational work paradigms, particularly in implementing work from home (WFH) systems as alternatives to conventional work from office (WFO), significantly impacting administrative employee performance. This study aims to analyze factors influencing administrative employee performance in WFO and WFH modalities, compare the effectiveness of both work systems, and identify best practices for performance optimization. The research employed a quantitative approach with comparative study design, involving 300 administrative employee respondents equally distributed between WFO and WFH groups. Data were collected using validated structured questionnaires with 5-point Likert scales, measuring task performance, contextual performance, adaptive performance, work-life balance, technological self-efficacy, and organizational support. Data analysis utilized independent sample t-tests and MANCOVA using SPSS 29.0. Results indicate no significant differences in overall performance between WFO and WFH, but specific dimensional differences were found where WFO excelled in task performance while WFH was superior in adaptive performance. Work-life balance emerged as the primary performance determinant with the largest contribution, followed by technological self-efficacy and organizational support. Findings confirm that work modality effectiveness depends on the balance of organizational, individual, and technological factors in supporting administrative objective achievement. Keywords: administrative performance; work from home; work from office; work-life balance; technological self-efficacy